Representations of the Holy Family Trips in the Art of the 5th-15th Centuries - Grau-Dieckmann, Patricia (Eikón / Imago, 2012)
In Christian art there are scenes in the life cycles of the Virgin Mary and Jesus that, though familiar and known, possess an iconographic content that does not respond strictly to the canonical Gospel accounts. Engendered in the bosom of the Church, they also derived from apocryphal stories and legends and oral traditions. In this context, this paper will examine different ways of representing the Holy Family trips during the period between the V and XV, seeking to explain the popularity of such scenes.